INSTITUTIONAL CONTEXT OF WIND ENERGY AND IMPACTS ON TRADITIONAL COMMUNITIES IN THE COASTAL ZONE OF NORTHEAST BRAZIL, BETWEEN 2000-2020 - Aguiar Silva, Lígia de Nazaré; Rojas Pinilla, Humberto; Felipe Fernandes, Juana Angelica (Mercator; Vol 22 (2023), 2023)
Since the arrival of the wind industry in Brazil, the coastal area of the northeast has been home to wind farms. In addition to concentrating wind farms, this area is characterized by traditional communities, which has generated environmental impacts in these territories. We therefore sought to analyze how the government, through the mechanisms and practices adopted, has contributed to the expansion of this industry in Ceará despite the increase in environmental impacts on the communities affected. A qualitative analysis was used, using secondary data such as legislation and bibliographic sources, with the study centered on discourse, practices, and the correlation between data. We identified the reduction of bureaucracy in environmental licenses and the creation of specific monetary funds for the sector, which proved to be effective in boosting the presence of wind farms. The legislation, however, does not have instruments to protect the communities affected nor encourage social participation in the process of planning and installing wind farms. At the municipal level, municipalities have no regulatory instruments for this activity in their territories. Understanding the weaknesses and strengths of governmentality will help build laws and practices that serve the wind industry and communities. Keywords: